POTRET PEMOTONGAN DAN PEMUNGUTAN PAJAK OLEH BENDAHARA DANA BANTUAN OPERASIONAL SEKOLAH (BOS) - Nur Handayani; Maratus Zahro (Universitas Negeri Padang, 2021)
This study aims to examine the implementation of tax deductions and collection by the Treasurer of Bantuan Operasional Sekolah (BOS). The research data analysis used a descriptive qualitative approach. The research objects were SD Negeri Banyuajuh 3 Kamal Bangkalan Madura and SMK Kesehatan Yannas Husada Bangkalan. Data collection techniques used unstructured interviews, observation and documentation. The results showed that the implementation of witholding tax and levy carried out by the treasurer at SD Negeri Banyuajuh 3 Kamal Bangkalan Madura and SMK Kesehatan Yannas Husada Bangkalan was still not optimal and some were not in accordance with the applicable taxation regulations. The results show that there are five (5) things that can make the treasurer make the mismatch, namely: first, the high incomprehension of the treasurer about tariffs, the basis for imposition and obligations related to taxation. Second, the lack of training attended by BOS fund treasurers. Third, the rapid change in taxation rules. Fourth, lack of socialization from related parties (such as the Tax Service Office, Education and Culture Office). Fifth, the high level of activity apart from taking care of BOS funds from the BOS fund treasurer. This mismatch automatically causes the tax, which is generally the state revenue that is relied on the most to become less than optimal. This is because there are still funds that should go to the state treasury. Keywords: Treasurer; BOS Funds; Deductions; Collections; Taxes